Chromatin Structure of the Simian Virus 40 Late Promoter: a Deletional Analysis - Friez, Michael (American Society for Microbiology, 1999)
The goal of this study was to determine the minimal sequence within the simian virus 40 (SV40) late promoter region, nucleotides (nt) 255 to 424, capable of phasing nucleosomes as measured by its ability to confer the greatest endonuclease sensitivity on adjacent DNA sequences. To identify the minimal sequence, a deletional analysis of the late region was performed by utilizing a SV40 recombinant reporter system. The reporter system consisted of a series of unique restriction sites introduced into SV40 at nt 2666. The unique restriction sites allowed the insertion of test sequences as well as measurement of conferred endonuclease sensitivity. The results of the deletional analysis demonstrated that constructs capable of conferring the greatest nuclease sensitivities consistently included nt 255 to 280. The activator protein 4 (AP-4) and GTIIC transcription factor binding sequences lie within this region and were analyzed individually. Their abilities to confer nuclease sensitivity upon the reporter nearly matched that of the entire late domain. These results suggest that transcription factors AP-4 and transcription-enhancing factor which binds the GTIIC sequence are able to confer significant levels of nuclease sensitivity and are likely involved in the formation of the SV40 nucleosome-free region.